1990
DOI: 10.1101/gad.4.3.380
|View full text |Cite
|
Sign up to set email alerts
|

Human gamma- to beta-globin gene switching in transgenic mice.

Abstract: Previous studies demonstrated correct tissue-and temporal-specific expression of human 7-and ~-globin genes in transgenic mice; however, expression was extremely low. When the erythroid-specific DNase I superhypersensitive (HS) sites that are normally located upstream of the human 13-globin locus were fused individually to 7" or 13-globin genes, expression increased to endogenous mouse globin levels but temporal specificity was lost. In contrast, when the HS sequences were combined with fragments containing bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
197
2
10

Year Published

1993
1993
2001
2001

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 289 publications
(215 citation statements)
references
References 21 publications
6
197
2
10
Order By: Relevance
“…β -globin gene is silenced in embryonic and fetal erythroid tissue. Later, a similar stage specific expression has also been obtained with γ-globin gene [5,6]. These results have led to the suggestion that cis-acting regulatory elements closely associated with the human β and γ globin genes could confer tissue-and temporal-specific expression [5,6].…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…β -globin gene is silenced in embryonic and fetal erythroid tissue. Later, a similar stage specific expression has also been obtained with γ-globin gene [5,6]. These results have led to the suggestion that cis-acting regulatory elements closely associated with the human β and γ globin genes could confer tissue-and temporal-specific expression [5,6].…”
Section: Discussionmentioning
confidence: 59%
“…Previous studies in transgenic mice have shown that human β -globin gene alone is expressed specifically in adult erythroid tissue in a temporal pattern parallelling that of the endogenous mouse β-globin genes [5,6,19,20]. β -globin gene is silenced in embryonic and fetal erythroid tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The PCR product was then digested with an A ␥ globinspecific restriction enzyme-PstI-and analyzed on a denaturing 7 M urea 6% polyacrylamide gel. In addition, the relative quantities of ␤ and ␥ globin mRNA from reticulocytes were analyzed by primer extension [25]. The ␤: (5Ј-CCACAGGGCAGTAACGGCAGA-3Ј) and ␥ (5Ј-CCAGCATCTTCCACATTCACC-3Ј) globinspecific oligonucleotides were 32 P end-labeled, hybridized with 10 ng of total reticulocyte RNA, and extended with reverse transcriptase (AMV, Promega).…”
Section: Detection Of ␥ and ␤ Globins And Their Transcriptsmentioning
confidence: 99%